Le POC : bulletin de liaison des Frontrunners de Paris. (Paris : Frontrunners Paris, 1996)
Fonds Suzan Daniel (FSD)
Periodiciteit: tweemaandelijks
Redactie: BP 120, 75623 Paris Cedex 13
Frans
Periodiek